Research of statistical rows which consist of random numbers - Єгоров, С.В. (Proceedings of National Aviation University (archive), 2010)
Modeling by a method of Monte-Carlo casual samples from a general totality for the purpose of definition of probability of non-failure operation is spent. It is carried out the analysis of statistical numbers which consist of random numbers